2023
DOI: 10.1167/iovs.64.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Corynebacterium mastitidis to Better Understand the Ocular Microbiome

Abstract: Purpose Corynebacterium spp. are Gram-positive bacteria commonly associated with the ocular surface. Corynebacterium mastitidis was isolated from mouse eyes and was demonstrated to induce a beneficial immune response that can protect the eye from pathogenic infection. Because eye-relevant Corynebacterium spp. are not well described, we generated a C. mast transposon (Tn) mutant library to gain a better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…St. Leger and Caspi [ 44 ] isolated Corynebacterium mastitidis ( C. mastitidis ) from the conjunctiva of a group of C57BL/6 mice housed at the National Institutes of Health and demonstrated that C. mastitidis is able to form a stable ocular colonines in mouse eyes. This species has been used in mouse models to study how the ocular microbiome affects the ocular surface immune homeostasis [ 45 ]. To our knowledge, this organism has not been isolated from human ocular infection.…”
Section: Gram-positive Ocular Pathogensmentioning
confidence: 99%
“…St. Leger and Caspi [ 44 ] isolated Corynebacterium mastitidis ( C. mastitidis ) from the conjunctiva of a group of C57BL/6 mice housed at the National Institutes of Health and demonstrated that C. mastitidis is able to form a stable ocular colonines in mouse eyes. This species has been used in mouse models to study how the ocular microbiome affects the ocular surface immune homeostasis [ 45 ]. To our knowledge, this organism has not been isolated from human ocular infection.…”
Section: Gram-positive Ocular Pathogensmentioning
confidence: 99%